The Economic Journal the quarterly journal of the Royal Economic Society. - Royal Economic Society (Great Britain).; British Economic Association (London Macmillan, 1891)
Each volume of the Economic Journal feature: a selection of the best new work in theoretical and empirical economics, a new Policy Forum; an extensive book review section; regular specially-commissioned survey articles; and a regular Software Review section.
Subtitle varies slightly.
Available for University of the Philippines - Diliman School of Economics via JSTOR Econlit. Click here to access http://www.jstor.org/action/showPublication?journalCode=economicj
Fulltext available at JSTOR and EBSCO Business Ultimate
Vols. for 1891-1902 issued by: British Economic Association; 1903- by: Royal Economic Society.
Keywords: Economics -- Periodical